Determinants of Adverse Events in Patients with Cancer Who Practiced Self-Medication: A Cross-Sectional Study in Southwestern Uganda - Godwin Nimusiima; Sarad Pawar Naik Bukke; Awad Osman Abdalla Mohamed; John Martin Tumwebaza; Radiana Makuza Kabera; Joel Sebisaalu; Amina Abubakar; Patrick Kitheka Muasya; Bayapa Reddy Narapureddy; Nyakato Caroline; Silas Ojuka; John Isiiko; et al. (Cancer Management and Research, 2026)
Background: Cancer therapies have been the cornerstone in cancer care. Co-morbidities and Adverse Events (AEs) often encourage some patients with cancer to resort to self-medication in search of relief or better symptom management. While self-medication is a key aspect of self-care and may offer some relief, it also poses risks, especially the potential for AEs. Limited data exist in Uganda, particularly at the Mbarara Regional Referral Hospital (MRRH) Cancer Unit, regarding the prevalence and determinants of AEs. Objective: To determine the prevalence and factors associated with AEs among self-medicating cancer patients at the MRRH Cancer Unit. Methods: A cross-sectional study was conducted from 1st of February to 31st of March 2025, among patients with cancer attending the MRRH Cancer Unit. Using Cochran’s formula, the sample size was estimated to be 270 patients who were recruited using consecutive sampling technique. Data were collected using interviewer-administered questionnaires and patient records, with medica tion reconciliation performed to identify both prescribed and self-medicated drugs and herbal products. AEs were graded using the Common Terminology Criteria for AEs. Descriptive statistics and binary logistic regression tests were performed using STATA version 17.0 employing and binary logistic regression tests. Results: Out of 270 participants, 218 (80.7%) experienced AEs. Grade 1 was the most common (49.8%) followed by grade 2 (41.4%), and grade 3 (8.8%). The determinants of AEs included the use of alkylating agents (AOR=3.6, 95% confidence interval CI: 1.02–12.51; p-value= 0.046), self-medication with drugs for acid-related disorders (AOR=7.9, 95% CI: 1.79–35.41; p-value=0.006) and herbal medicines use (AOR=2.1, 95% CI: 1.09–4.22; p-value=0.026). Conclusion: AEs among self-medicating patients with cancer are highly prevalent at MRRH cancer unit. Therefore, implementing comprehensive medication review in this population, and applying active ADE risk classification and closer monitoring in high-risk patients, including those on any alkylating agents and those who use herbal products, is crucial to minimize the ADEs and ensure safe use these products.
Keywords: self-medication; determinants; chemotherapy; adverse events; cancer; Uganda